An In Vitro Verification of the Effects of Paeoniflorin on Lipopolysaccharide-Exposed Microglia. (12th October 2020) - Chen, Qiliang; Liu, Yaojun; Zhang, Yuanyuan; Jiang, Xinyu; Zhang, Yuqin; Asakawa, Tetsuya
Abstract : Background . The neuroprotective effects of Paeoniflorin (PF) are well known. Most of the evidence was verified in vivo . We attempted to perform an in vitro verification of the effects of PF in microglia. Methods . A lipopolysaccharide- (LPS-) exposed microglia model was employed. An enzyme-linked immunosorbent assay was used to measure the levels of cytokines in the culture supernatants. A real-time polymerase chain reaction was performed to measure the mRNA expression of cytokines and M1- and M2-like genes. A western blot analysis was used to examine the expression of proteins associated with the nuclear factor-kappa B (NF- κ B) signaling pathway. Results . We found that the administration of PF reversed the inflammatory response induced by LPS. It downregulated proinflammatory cytokines and upregulated anti-inflammatory cytokines. This, in turn, alleviated the oxidative injuries, downregulated the expression of M1-like genes, and upregulated the expression of M2-like genes. PF can also reverse the changes in proteins associated with the NF- κ B signaling pathway induced by LPS. Conclusions . We provided evidence obtained in vitro concerning the neuroprotective effects of PF via suppressing activation of microglia, which might be associated with the NF- κ B signaling pathway. These findings contribute to obtaining a deeper understanding of PF, a potential new treatment for brain injuries.